2006
DOI: 10.1121/1.2216906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of level and frequency on the audibility of partials in inharmonic complex tones

Abstract: The effect of level and frequency on the audibility of partials was measured for complex tones with partials uniformly spaced on an equivalent rectangular bandwidth (ERB(N)) number scale. On each trial, subjects heard a sinusoidal "probe" followed by a complex tone. The probe was mistuned downwards or upwards (at random) by 4.5% from the frequency of one randomly selected partial in the complex. The subject indicated whether the probe was higher or lower in frequency than the nearest partial in the complex. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 38 publications
10
51
0
Order By: Relevance
“…According to this 1-dB criterion, for the stimuli used here ͑including the pink noise background͒, harmonics of the 200-Hz nominal-F0 complex were resolved up the seventh; the eighth and higher harmonics were unresolved. This is broadly consistent with the conclusions of several psychoacoustic studies in which direct measures of the ability to hear out harmonics were obtained ͑Plomp, 1964; Moore and Ohgushi, 1993;Moore et al, 2006͒, and one harmonic below that at which Bernstein and Oxenham ͑2006͒ estimated that the transition region between good and poor DLF0s occurred for F0s of around 175 Hz at moderate levels. 2 We also tested other values for the criteria.…”
Section: E Excitation Pattern Simulationssupporting
confidence: 77%
“…According to this 1-dB criterion, for the stimuli used here ͑including the pink noise background͒, harmonics of the 200-Hz nominal-F0 complex were resolved up the seventh; the eighth and higher harmonics were unresolved. This is broadly consistent with the conclusions of several psychoacoustic studies in which direct measures of the ability to hear out harmonics were obtained ͑Plomp, 1964; Moore and Ohgushi, 1993;Moore et al, 2006͒, and one harmonic below that at which Bernstein and Oxenham ͑2006͒ estimated that the transition region between good and poor DLF0s occurred for F0s of around 175 Hz at moderate levels. 2 We also tested other values for the criteria.…”
Section: E Excitation Pattern Simulationssupporting
confidence: 77%
“…He demonstrated that subjects were able to hear out only the first five to eight harmonics. More recent data confirm these results [5][6][7]. Pattern-recognition theories therefore predict that the lower resolved harmonics (up to the eighth) should be dominant in determining the pitch of complex tones.…”
Section: Introductionsupporting
confidence: 72%
“…Two complex tones comprising four components served as the standard and comparison tones. Two of the components within these tones were incremented by 7 dB to Decay uncovered in nonverbal short-term memory 11 create a change to the spectral profile, and the frequencies of the components were adapted from those used by Moore, Glasberg, Low, Cope, and Cope (2006). See Table 1 All individuals began the study with a number of training sessions, contrasting the standard and comparison tones over a silent 2 s interval until they could reliably perform the discrimination.…”
Section: Resultsmentioning
confidence: 99%